Variabilidade espacial da resistência à penetração e do teor de água em solo cultivado com cana-de-açúcar no litoral sul potiguar - Medeiros, Jonatan Levi Ferreira de (Universidade Federal Rural do Semi-Árido, 2015)
Soil parameters like penetration resistance (RSP), water content and bulk density are important attributes for studying aspects of soil physical degradation like compaction. In light of this, this work had as objective identifying, mapping and also to use criteria for interpreting data of RSP and soil moisture aiming the planning of soil management practices in areas cropped with sugarcane. Sampling was carried out in a grid whose points at 100x100 meters by referenced from one point to another. Data was taken until 40 cm depth by means of an electronic penetrometer mounted on an All Terrain Vehicle, for RSP, and a TDR probe for soil moisture content. Afterwards, geostatistical procedures were used for data interpolation and drawing of contour maps, from which compaction intensity was evaluated aiming at future management decisions. The best model fit the spherical semivariogram were to exponential RSP variable to the soil water content. Moderate to strong spatial dependency of RSP allowed unbiased estimation of values for non sampled locations minimizing estimative errors. For RSP, the range was adequate the situation of the research, where the minimum observed value reached 183, appropriate result to the sample grid of field collections, differently the water content in soil showed range less than 100 meters. Soil water content did not influence directly RSP values. Contour maps showed that RSP is heterogeneous at the field scale and that site specific management practices can be applied, mainly to reduce the effect of compression depths greater than 20 cm
Spatial variability of penetration resistance and water content in soil cultivated with cane sugar Natal south coast
Keywords: soils; Sugar cane; Penetration-soil; Damp soil; Mapping; Solos; Cana-de-açúcar; Penetração-solo; Umidade-solo; Mapeamento; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO